2011
DOI: 10.1017/s0263034611000218
|View full text |Cite
|
Sign up to set email alerts
|

Image analysis of expanding laser-produced lithium plasma plume in variable transverse magnetic field

Abstract: Using fast imaging technique, the effect of transverse magnetic field on the shape and dynamics of the lithium plasma plume has been studied. Enhancement in the overall emission intensity as well as appearance of distinct structures (lobes) in the plasma plume in the presence of magnetic field has been observed. By introducing a variable magnetic field, the influence of J × B force in expanding plasma plume across the transverse magnetic field has been explored. It appears that J × B force does not has a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
(34 reference statements)
2
11
0
Order By: Relevance
“…Many research groups have investigated the interaction of magnetic field with expanding plasma and observed some interesting phenomena, such as ion acceleration/ deceleration, spectral emission intensity enhancement, electron density and temperature increase, plasma plume splitting, instability and oscillating behavior and so on [13][14][15][16]. Ajai Kumar et al [17][18][19][20] investigated the effect of magnetic field on the lithium plasma plume emission. Enhancement in the emission intensity and different structures of plasma plume in the presence of magnetic field have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have investigated the interaction of magnetic field with expanding plasma and observed some interesting phenomena, such as ion acceleration/ deceleration, spectral emission intensity enhancement, electron density and temperature increase, plasma plume splitting, instability and oscillating behavior and so on [13][14][15][16]. Ajai Kumar et al [17][18][19][20] investigated the effect of magnetic field on the lithium plasma plume emission. Enhancement in the emission intensity and different structures of plasma plume in the presence of magnetic field have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from the spectra that the intensity of the ionic lines increased significantly with B-field presence, while the changes are minimal for neutral lines. Interestingly, for transverse magnetic field case the ionic spectral line does not exhibit any significant change with both, magnetic field and ambient gas (Kumar et al, 2011a;2011b). Figures 5 and 6 show the line intensities of Sn I (563.17 nm) and Sn II (556.19 nm) with distance from the target.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies employing a LPP expanding into a transverse B field showed that conversion of the plasma thermal energy into kinetic energy, plume confinement, ion acceleration, emission enhancement, plasma instabilities, etc. (Neogi & Thareja, 1999;Rai et al, 2003;Harilal et al, 2004;2005a;2005b;Pagano & Lunney, 2010;Kumar et al, 2011a;2011b;Pandey & Thareja, 2011). A B-field is capable of providing such a control by influencing the dynamics, ionization, and optical properties of a LPP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Structures developed in the expanding plasma were also studied by fast imaging and were attributed to atomic processes in the plasma. 10 The emission intensity from different species in the plasma was also observed to be influenced by the applied magnetic field and was attributed to magnetic confinement. 11,12 An enhancement of 2.6 in the deposition rate was obtained in the presence of a magnetic field in case of film deposition of copper.…”
Section: Introductionmentioning
confidence: 98%